Kunst und Frömmigkeit in Göttingen: die Altarbilder des späten Mittelalters - Noll, Thomas; Warncke, Carsten-Peter (Deutscher Kunstverlag, 2012)
The present volume of essays introduces all of the completely or mostly preserved altarpieces in Göttingen from the late Middle Ages. As such, the book offers fundamental groundwork and focuses on an art region, whose late medieval culture has received little consideration before now